Experimental research on the shear-rate-dependent shear strength of rock-like joints. Issue 4 (October 2021) - Yuan, W; Li, J C
Abstract: Shear strength is one of the most important strength parameters of rock joints, and it is also a primary parameter for the design and safety evaluation of rock mass structures. In view of the characteristic of variable deformation rates of rock joints subjected to dynamic disturbance, direct shear tests of rock-like joints under different shear displacement rates are carried out, and the law of shear strength changing with shear displacement rate is explored. The samples include planar and undulating joint samples and intact cubic samples, among which the undulation angles of undulating joints include 15° and 30°. The normal boundary of joints is a constant normal pressure. Shear displacement rates are set to 5 different values, including 2.3 mm/min, 7.6 mm/min, 13.1 mm/min, 22.2 mm/min and 47.2 mm/min. The experimental results show that the change of shear strength with shear displacement rate is related to the tangential deformation mode of joints. For planar joints and 15° undulating joints, the tangential deformation is dominated by sliding, and the shear strength decreases with the increase of shear displacement rate. While for 30° undulating joints and intact samples, the main characteristic of tangential deformation is snipping, which is caused by material failure, and the shear strength increases with the increase of the shear displacement rate. The mechanism may be that the shear strength of shear-sliding-type joints is derived from the inherent friction of the joint contact surfaces, while the shear strength of snipping-type joints is mainly dominated by the material strength of asperities. The inherent friction of contact surfaces decreases with shear displacement rate. However, the shear strength of material increases with increase of the shear displacement rate.